Cirrus : infraestrutura de e-science para contexto ambiental - Guarienti, César Eduardo (2016)
The environmental area uses computational resources to support their research, mainly in the automation of activities such as: communication, proposition, hy- pothesis testing and simulation models. In recent years the amount of data ge- nerated has reached gigantic proportions, thus the handling and interpretation of this information requires the use of new techniques and infrastructure that minimally meet those needs. Thus, this study aimed to build and deploy the Cirrus environment, which is an infrastructure it e-science based on cloud com- puting technologies that favors the use of scientific computing with a unified Web access. To validate the environment were tested various software related to the environmental area, as well as the possibility of use of various operating systems. The results show that it is viable the environment of use e-science for scientific use providing an infrastructure that supports the different needs of the Graduate Studies Program in Environmental Physics (PPGFA) of the Federal University of Mato Grosso (UFMT).